2007
DOI: 10.1007/s10540-007-9044-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mitochondria in Stem Cell Biology

Abstract: This mini-review summarizes the current literature on the role of mitochondrial DNA mutations and mitochondrial metabolism in stem cell biology. The possible uses of stem cells as a therapeutic tool in mitochondrial disorders are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 39 publications
1
33
0
Order By: Relevance
“…Our study confirms and provides more detailed evidences for the suggestion of other authors that stemness may be estimated using certain functional mitochondrial characteristics [8], indicating that along with the numerous changes in cell infrastructure, including the redistribution of mitochondria, an increase in the unusually low mitochondrial NADH content may serve for the noninvasive fluorescence measurement based monitoring of the development of complex differentiation processes. Thus, we suggest that an increase in NAD(P)H fluorescence may be useful for a non-invasive detection of the onset of myoblast differentiation.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Our study confirms and provides more detailed evidences for the suggestion of other authors that stemness may be estimated using certain functional mitochondrial characteristics [8], indicating that along with the numerous changes in cell infrastructure, including the redistribution of mitochondria, an increase in the unusually low mitochondrial NADH content may serve for the noninvasive fluorescence measurement based monitoring of the development of complex differentiation processes. Thus, we suggest that an increase in NAD(P)H fluorescence may be useful for a non-invasive detection of the onset of myoblast differentiation.…”
Section: Resultssupporting
confidence: 87%
“…Recently, some authors have suggested a hypothesis that stem cell competence (i. e. stem cell stability and pluripotency) may be estimated using functional mitochondrial characteristics [8]. Lonergan et al [2] found that several mitochondrial properties, such as subcellular localization and metabolic activity, can be considered as markers of "stemness".…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, information is sparse concerning how exactly CD44 may affect mitochondrial function. Stem cell mitochondria have recently come under increased scrutiny because new information has revealed their role in numerous cellular processes, beyond ATP production and apoptosis regulation, suggesting mitochondria to serve as a cell fate or lineage determinant [5052]. Thus, hyaluronan influence on mitochondrial properties may at least to some extent affect stem cell self-renewal and differentiation.…”
Section: Influence Of Hyaluronan On Stem Cell Behaviormentioning
confidence: 99%
“…Beside their well-known function in energy supply, mitochondria play pivotal roles in other essential cellular processes, such as the formation of Fe-S-clusters, calcium homeostasis, oxygen sensing, cellular proliferation, apoptosis and aging [1]. By now it is becoming evident that mitochondria are also important for cell differentiation processes [2], [3], [4].…”
Section: Introductionmentioning
confidence: 99%